The Sublime for the Living: A Dialogue (Itinera, 2021)
Following the tradition of the philosophical dialogue, we reimagine our real conversation where we come to understand our respective views on the sublime. We aim to do so in a way that respects both the sublime’s complex philosophical past and its emerging future in empirical research. As in a traditional dialogue, this contrivance is supposed to enact a philosophical exchange. The following conversation reveals the interlocutors’ diverging, converging, and shifting understanding of the sublime in a way that a verbatim interview transcript or a co-authored treatise could not. Moreover, its setting is indicative of the conversation’s current moment: the scene is the virtual Zoom room.
Keywords: sublime, history of aesthetics, awe, empirical aesthetics